2014
DOI: 10.4236/ojer.2014.31004
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Altitude Observed on the Occasion of the Tohoku Earthquake (M = 9.0) Occurred on March 11, 2011

Abstract: Since October 1, 2010, a GPS receiver is put into operation at Tokai (Japan) in an experiment on Neutrino Physics (T2K). A significant variation of the altitude was detected from the beginning of March 2011, so that it has made worthwhile to investigate the possibility that such variations could be correlated to the Tohoku earthquake. In order to investigate in details this possibility, we analyzed the GPS data collected during 2011 by GEONet the GPS Earth Observation Network (GEONET). GEONET is the GPS networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“… Chen et al [2011] have found from the analysis for many EQs in Taiwan that significant surface changes are observed several days before an EQ (when we have a lot of seismo‐electromagnetic phenomena). The similar analyses by using the GPS data have been carried [ Milillo et al , 2012; K. Hattori, private communication, 2012], which have reported similar pre‐EQ surface variations. Of course, we need much more evidences on these surface variations, but we can say, at the moment, that a physical process has been identified to be really existing, producing the atmospheric oscillations (or AGW and/or AW).…”
Section: Conclusion and Discussionsupporting
confidence: 60%
“… Chen et al [2011] have found from the analysis for many EQs in Taiwan that significant surface changes are observed several days before an EQ (when we have a lot of seismo‐electromagnetic phenomena). The similar analyses by using the GPS data have been carried [ Milillo et al , 2012; K. Hattori, private communication, 2012], which have reported similar pre‐EQ surface variations. Of course, we need much more evidences on these surface variations, but we can say, at the moment, that a physical process has been identified to be really existing, producing the atmospheric oscillations (or AGW and/or AW).…”
Section: Conclusion and Discussionsupporting
confidence: 60%
“…Recently some researchers have tried to find some ground motions before an EQ on the basis of analyses of available GPS data, who have found that the ground motion is recognized several days before EQs (Chen et al, 2011;Milillo et al, 2012;Hattori, private communication, 2012). The presence of such a kind of ground motions would be a definite answer to our ad-hoc assumption of the AGW hypothesis.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Further, some "direct" evidence of this channel was recently provided by Asai et al (2011) on the basis of Doppler-shift observations of the real AGW in the seismo-ionospheric intercation, because the Doppler measurement provides the direct information about the ionosphere, unlike our previous study of AGW fluctuation in the sub-ionospheric VLF data. Important additional information is that some evidence has recently supported the ad-hoc assumption of the AGW concept: significant surface changes were observed several days before an EQ (Chen et al, 2011;Milillo et al, 2012;Hattori, private communication, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the biggest problem in the second atmospheric oscillation channel is that it is based on an ad-hoc assumption that there must be present some kind of precursory phenomena near the ground surface. There have been published a few papers that there occur some precursory ground movements in possible association with EQs by analyzing the GPS data (Chen et al, 2011;Milillo et al, 2012). So, there are very lacking works on the correlations between the ionospheric perturbations and ground effects before an EQ.…”
Section: Introductionmentioning
confidence: 99%